Comparison between gutta-percha and Resilon removal using two different techniques in endodontic retreatment - de Oliveira, D. P.; Barbizam, JVB; Trope, M.; Teixeira, F. B. (Elsevier B.V., 2006)
This study compared the remaining filling material and working time when removing gutta-percha/AH 26 and Resilon/Epiphany from root filled extracted teeth. The root fillings were removed using chloroform and two different rotary systems (K3 and Liberator files). The amount of residual filling material on the canal walls was imaged and measured using image analyzer software. The group filled with Resilon/Epiphany and retreated with K3 files demonstrated the least residual filling material on the walls (p < 0.05). There was no statistically significant difference between the guttapercha/AH26 and Resilon/Epiphany groups when the Liberator files were used (p > 0.05). In the groups filled with Resilon/Epiphany, the filling was removed faster than groups filled with gutta-percha/AH 26 (p < 0.05). K3 rotary system was faster than Liberator to remove both gutta-percha and Resilon (p < 0.05). Resilon/ Epiphany was effectively removed with K3 or Liberator rotary files.
Keywords: endodontic retreatment; Resilon; rotary files